A Study on Exit Interview: Management Tool to Retain Employees - Singh, Smita (Journal of Commerce and Trade, 2019)
Exit interviews are raising trend in the organization, it is conversation conducted by the human resource department when an employee is leaving the company. This conversation can be oral as well as written. These interviews help the organization in providing feedbacks which open the area of improvement for the company and many times these interviews also work as management tool to retain employees. Exit interviewing is one of the most widely used methods of gathering employee feedback. The main objective of the paper is to the study the concept the of exit interview and to analyze how these interview work as the management tool to retain employees or diminishing employee turnover. Moreover the study also focuses on the significance and the challenges faced by the human resource staff in conducting exit interviews. Classification-JEL : M12, J28